European Higher Education: Looking Back, Looking Forward - Sursock, Andrée (International Higher Education, 2021)
Up until 2010, reforms were relatively coherent across Europe, owing to a number of European-wide processes. However, the lingering impact of the 2008 financial crisis, combined with international rankings, resulted in a fragmented policy landscape and a relative “loss of appetite” for European policies. If managed judiciously, a new European initiative has the potential of bringing the continent together again.